El bien jurídico en el derecho penal. Algunas nociones básicas desde la óptica de la discusión actual - Kierszenbaum, Mariano (2009)
The notion of "legally protected interest" has served, to date, relevant\npurposes in the study of Criminal Law: it has been used as criterion for the classification of crimes and as a boundary for Criminal Law. In that way, the notion\nof "legally protected interest" has been used by liberalism as a restraining barrier for punitive power. But the understanding of ?legally protected interest? as a coercion-reducing notion is currently undergoing one of the most serious crisis ever. The harshest criticism comes from Jakobs, within German scholars, and from Sancinetti, within Argentine ones. The purpose of this work is to briefly explain current discussions regarding whether the notion in question is significant or not according to current theories